Poor implementation of tobacco control measures and lack of education influences the intention to quit tobacco: a structural equation modelling approach - Mir Faeq Ali Quadri; Tenny John; Damanpreet Kaur; Maryam Nayeem; Mohammed Khaleel Ahmed; Ahmed M. Kamel; Santosh Kumar Tadakamadla; Vito Carlo Alberto Caponio; Lorenzo Lo Muzio (BMC, 2022)
Abstract Background Tobacco consumption remains a public health issue and is one of the major causes of death in India. This study presents a validated conceptual model to assess the interaction between education, perceived application of tobacco control measures, type of tobacco and their effects on the intention to quit tobacco. Additionally, the direct and mediating roles of tobacco use -frequency, -duration, and -dependency on the intention to quit is also investigated. Methods An analytical cross-sectional study was carried out, and data from tobacco users of six randomly selected states in India was collected via face-to-face interviews. Structural equation modeling (SEM) was performed using R v 3.6.3 to test the model fit and to explore the association between tobacco control measures and the intention to quit tobacco. Results From 1962 tobacco users, 43.7% wanted to quit tobacco immediately. Tambakoo (57.7%) was the most common type of tobacco used and 68.9% said that minors could buy tobacco. Findings from SEM showed that that one standard deviation (SD) increase in the perceived application of tobacco control measures is directly associated with a 0.181 SD increase in the intention to quit tobacco (B = 0.181, P < 0.001), and this effect was partially mediated by frequency of tobacco consumption (B = 0.06, P < 0.05). Also, a better education level was associated with a higher intention to quit tobacco (B = 0.14, P < 0.001). Conclusions To conclude, the application of tobacco control measures and a better education level may positively affect the intention to quit tobacco. The frequency of tobacco use and the number of influencers play an essential role in deciding to quit. In future, longitudinal studies are recommended to further substantiate the evidence.